Identificación y análisis de factores de continuidad de las PMO en grandes empresas colombianas (2015)
In the present document, Management Plan of the degree work titled "IDENTIFICATION AND ANALYSIS OF CONTINUITY FACTORS OF THE PMO IN COLOMBIAN LARGE COMPANIES", the authors will establish the conditions with which the managerial work of the same will be carried out. The following components are included in this delivery: B. Initiation stage: - The letter of constitution of the degree work, - The registration of stakeholders. C. Planning stage: - The analysis and management strategies of the stakeholders, - The documentation of requirements and the traceability matrix, - The scope statement, - The WBS of the project with its dictionary, - The time and cost baselines, - The quality plan, - The organization chart of the degree work, - The matrix of assignment of responsibilities, - The communications matrix, and - The risk register including identification and response plans. D. Formats: - Performance report, - Of requests for change, - Quality control, - Meeting minutes, - Of lessons learned, - Formalization of the acceptance of the product of the degree work, and - Contribution of the work of degree to the Master. Based on these components, the appropriate performance indicators will be identified for effective management in the execution phase, using monitoring and control tools, which will allow early detection and correction of deviations related to the triple restriction of time, cost and scope. .